Comparative Antimicrobial Activity of Commercial Wound Care Solutions on Bacterial and Fungal Biofilms. Issue 4 (October 2019) - Harriott, Melphine M.; Bhindi, Nayan; Kassis, Salam; Summitt, Blair; Perdikis, Galen; Wormer, Blair A.; Rankin, Timothy M.; Kaoutzanis, Christodoulos; Samaha, Mario; Stratton, Charles; Schmitz, Jonathan E.
Abstract : Background: Biofilms represent a complex milieu of matrix-enclosed microorganisms, which can significantly contribute to the pathology of chronic wounds. In this study, we compare the activity of 3 commercial antimicrobial wound care solutions, Vashe (HOCl based), PhaseOne (HOCl based), and Sulfamylon (mafenide acetate), for their in vitro activity against bacterial and fungal biofilms. Methods: Reference and clinical isolates of 6 Gram-negative bacterial species (36 total strains), 3 Gram-positive bacteria (21 strains), and 3 Candida species (9 strains) were used to create biofilms. Various working concentrations of the 3 antiseptic agents were incubated with the biofilms in microwell plates; they were monitored from 1 minute to 24 hours to compare bacterial and fungal viability through colony forming unit analysis. Results: Vashe and PhaseOne displayed excellent bactericidal and fungicidal activity, whereas Sulfamylon demonstrated minimal activity against the biofilms tested. With the exception of Candida albicans, all biofilms were eliminated at either 1 or 10 minutes using Vashe and PhaseOne solutions. In most cases, mafenide was unable to eliminate both bacterial and fungal biofilms, even with 24 hours of treatment. Conclusions: Biofilms represent a major clinical challenge, with no clear consensus for treatment of chronic wounds or prosthetic devices. Our results suggest that hypochlorous acid–based wound solutions such as Vashe and PhaseOne are more efficacious than mafenide in eliminating bacterial and fungal biofilms. Further studies are necessary to investigate and compare the in vivo efficacy of these products in clinical care. Abstract : Supplemental digital content is available in the text.